Impact pf pillars of social media marketing on the promotion of business / Aery Garney Francis - Francis, Aery Garney (Perpustakaan Tun Abdul Razak, Universiti Teknologi MARA Sarawak, 2022)
What is social media? Nowadays, social media is the one of the quickest ways in communication network to get connected, communicate and reach out the content and context. Social media is the tool for people to share the information globally. There are many opportunities created by the social media. One of them is to promote the small business mostly for their brand, business and customer’s access. The most of the product and service information will be shared through social media. This will build a trust and interaction. Social media create wide opportunities to all size business to promote their brand, create direct access to business and customers, precise about their product and services are shared and build stronger interaction with new and existing customers. By comparing traditionally and digital marketing methods promoting their product and services, traditional marketing methods need to invest more time, money and required high cost of labour. INTRODUCTION IMPACT OF PILLARS OF SOCIAL MEDIA MARKETING ON THE PROMOTION OF BUSINESS Moreover, advertising projection and distribution also require high cost of money and time. On the other side, digital marketing provides high efficiency in term of costing in promoting business. Utilization of effective social media tools can create the new methods of promoting businesses.